Open access – deus ex machina for publishing scholarly journals? (Libellarium: journal for research in the field of information and related sciences, 2016)
The article describes the evolution of scholarly communication through scholarly journals. It gives a short overview of the historical development, starting from the first journals in the 17th century to problems in the 20th century (such as increase in the number of journals, problems of accessibility, visibility, and journal access crisis). The open access (OA) movement is described. It arose from the “old tradition” facing new technologies and was supposed to be the solution to the journal crisis that culminated in 1990s. The idea, defined in the Budapest Open Access Initiative, was to assure free and unrestricted online availability of peer-reviewed journal literature. The beginnings of formal scholarly communication, back in 1665, had similar ideas of making research results available to the widest possible public. The idea was excellent – removing access barriers would increase visibility, impact and quality of research. Research has shown that OA articles have better impact and visibility (Lawrence, Brody, Harnad, Haajem, etc.). However, publishing scientific information has its costs. New models have been developed, some of them causing new restrictions and barriers. The most popular model is the author-pays model (article processing charges, APC) – if authors can afford to pay the processing charges, their work is published and thus more visible and more citable. However, if they cannot, a new problem arises – some research results, although valuable, are not published in open access and therefore they have lower visibility and impact. Another problem is the phenomenon of the so-called predatory publishers. Those publishers use the APC model but neglect quality control mechanisms in order to make profit. Their criteria for publishing are not positive peer-reviews but payments made by authors or their institutions. Predatory publishers’ practices are not only unethical, but also illegal, and they are a great threat to the development of science. New questions have arisen lately - has OA movement achieved its goal, has it evolved in the way it was supposed to, was it really dues ex machina for publishing scholarly journals, i.e. did it solve the access crisis. In conclusion, it is proposed that the solution to the problem of predatory publishers could be the development of a new set of information literacy skills that are based on finding, evaluating and properly using OA information. Universities and academic libraries should play an important role in developing those skills and competencies.
Keywords: open access; predatory publishers; scientific communication; scientific journals